New Approaches to Ancient Material Culture in the Greek & Roman World : 21st-Century Methods and Classical Antiquity - Cooper, Catherine, (Monumenta Graeca et Romana ;, 2021)
New Approaches to Ancient Material Culture in the Greek & Roman World is about Classical Archaeology at its broadest and is important reading to all Classicists. As part of a recent movement to highlight the rich diversity of the subject it overcomes traditional disciplinary boundaries to show the variety of current approaches to the study of Classical Antiquity from the Late Bronze Age to the Late Antique period. The multi-disciplinary papers deal with archaeology and art history, museum objects and fieldwork data, ancient texts and material culture, archaeological theory and historiography, and technical and literary analysis. The international contributors discuss a selection of methodologies currently used to study ancient material, and illustrate their relevance through case studies which span the Greek and Roman world.